Implementation of Project-Based Learning to Increase Students' Interest in Learning Aqidah Akhlak at MI Negeri 2 Batam - Puteri, Yayuk Sri Rahma; Kholifah, Yeni; Royani, Yayan; Yatimah (MANDAILING GLOBAL EDUKASIA, 2024)
Learning Akidah Akhlak in Madrasah Ibtidaiyah (MI) aims to shape the character and morals of students according to Islamic teachings. However, the lack of interest in learning students in this subject is a challenge that needs to be overcome. One method that can be used to increase students' interest in learning is Project-Based Learning (PBL). PBL encourages students to be more active, creative, and involved in the learning process through real projects that are relevant to everyday life. This study aims to analyze the application of the PBL method in increasing the interest of students in learning class 3 MIN 2 Batam in learning Akidah Akhlak. This study uses a qualitative approach with a classroom action method involving observation, interviews, and documentation as data collection techniques. The results of the study showed that the application of PBL was able to increase student participation, deepen their understanding of the concept of commendable morals, and foster positive attitudes in everyday life. Thus, the PBL method can be an innovative alternative in improving the quality of learning Akidah Akhlak.